PROBLEMATIKA GURU DALAM ASESMEN DIAGNOSTIK PADA PELAJARAN PAI DI SMPN 2 PANTAI LUNCI SUKAMARA - Siti Rahmah; Salamah (As-Sulthan Journal of Education, 2025)
The implementation of diagnostik assessments in the Independent Curriculum is very important to support differentiated learning. However, teachers often face obstacles in diagnosing students' learning needs, especially in Islamic Religious Education (PAI) subjects. This study aims to determine the problems faced by teachers and the efforts made to overcome them. The study used a descriptive qualitative approach with interview, observation, and documentation techniques for PAI teachers at SMP Negeri 2 Pantai Lunci, Sukamara Regency. The results of the study showed that diagnostik assessments had been implemented, but were not optimal. The obstacles faced included lack of teacher experience, students who did not understand their learning styles, and limited time, facilities, and internet access. Teachers have made various efforts such as attending training, utilizing the Merdeka Mengajar Platform, guiding students personally, conducting periodic assessments, collaborating with parents and other teachers, and managing time well. In conclusion, diagnostik assessments need to be supported by teacher competence, adequate facilities, and appropriate implementation strategies in order to produce adaptive learning in accordance with the principles of the Independent Curriculum.